2023
DOI: 10.3389/fmed.2022.1054557
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine and booster hesitation around the world: A literature review

Abstract: The development of COVID-19 vaccines has helped limit the extent of the pandemic, which over the past 2 years has claimed the lived of millions of people. The Moderna and Pfizer COVID-19 vaccines were the first to be manufactured using mRNA technology. Since then, other manufacturers have built their own vaccines which utilize adenovirus vector, whole inactivated coronavirus, and protein subunit methods. Given the continued mutation of the SARS-CoV-2 virus, a booster of the COVID-19 vaccine offers additional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…Rapid vaccine development and the use of novel mRNA vaccine technology are factors that may be associated with COVID-19 vaccine acceptance. 31 , 32 More generally, factors that may influence decisions regarding vaccination include trust in the effectiveness/safety of vaccines and/or in the system that delivers them, perception of disease risk, structural and psychological factors related to access and pragmatics, proneness to extensive information searching, and willingness to protect others. 33 Our study does not address the root causes of coverage inequalities, and we thus do not know the relative importance of these potential determinants for the coverage differences we observe.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid vaccine development and the use of novel mRNA vaccine technology are factors that may be associated with COVID-19 vaccine acceptance. 31 , 32 More generally, factors that may influence decisions regarding vaccination include trust in the effectiveness/safety of vaccines and/or in the system that delivers them, perception of disease risk, structural and psychological factors related to access and pragmatics, proneness to extensive information searching, and willingness to protect others. 33 Our study does not address the root causes of coverage inequalities, and we thus do not know the relative importance of these potential determinants for the coverage differences we observe.…”
Section: Discussionmentioning
confidence: 99%
“…This is aligned with global trends that have shown that populations who are largely non-white or live in a collectivist society share a common attitude about the social responsibility to be vaccinated against COVID-19. 22,23 One study found that countries with predominantly collectivist cultures such as China, India, Peru, and South Korea had greatest support for requiring vaccines, while support for mandatory vaccines was lowest in Poland, Russia, and Germany. 23 There are obvious nuances to this statement, with vaccine uptake often depending on availability of supplies and services, as low vaccination uptake was often seen in African countries.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA vaccines and other vaccines can induce this response against the S protein [25]. Global vaccination rates range from 40-90% depending on the country [26]. This makes the serological diagnosis of SARS-CoV-2 infection difficult because it is impossible to distinguish antibodies against the S protein by infection vs. those produced by vaccination.…”
Section: Introductionmentioning
confidence: 99%